EFEKTIVITAS METODE LATIHAN INTERVAL KECEPATAN DAN KOORDINASI MATA-KAKI TERHADAP KECEPATAN TENDANGAN SABIT PENCAK SILAT - Syaifullah, Rony (Pendidikan Dan Kepelatihan Olahraga, 2009)
The objective of this research is to investigate the impact of speed interval training method and foot-eye coordination on the athlete?s competence in the sabit speed kick of pencak silat.The results of this research are: (1) The male athlete?s achievement of sabit speed kick with interval 1:3 approach method are more effective than interval 1:2 approach method; (2) The male athlete?s who have high achievement foot-eye coordination with interval 1:3 approach method obtained significantly higher achievement in sabit speed kick than interval 1:2 approach method; (3) There is not significantly different between achievement in sabit speed kick of the male athlete?s who have low achievement foot-eye with interval 1:3 approach method and interval 1:2 approach method; (4) The male athlete?s achievement of sabit speed kick with interval 1:3 approach method are more effective than interval 1:1 approach method; (5) The male athlete?s who have high achievement foot-eye coordination with interval 1:3 approach method obtained significantly higher achievement in sabit speed kick than interval 1:1 approach method; (6) There is not significantly different between achievement in sabit speed kick of the male athlete?s who have low achievement foot-eye with interval 1:3 approach method and interval 1:1 approach method; (7) The male athlete?s achievement of sabit speed kick with interval 1:2 approach method are more effective than interval 1:1 approach method; (8) The male athlete?s who have high achievement foot-eye coordination with interval 1:2 approach method obtained significantly higher achievement in sabit speed kick than interval 1:1 approach method; (9) There are not significantly different between achievement in sabit speed kick of the male athlete?s who have low achievement foot-eye with interval 1:2 approach method and interval 1:2 approach method; (10) There is a positive interaction between training method and achievement foot-eye coordination on male athlete?s achievement in sabit speed kick of pencak silat.